Phasor-based single-molecule fluorescence lifetime imaging using a wide-field photon-counting detector - Colyer, R. (2009)
Fluorescence lifetime imaging (FLIM) is a powerful approach to studying the immediate environment of molecules. For example, it is used in biology to study changes in the chemical environment, or to study binding processes, aggregation, and conformational changes by measuring Förster resonance energy transfer (FRET) between donor and acceptor fluorophores. FLIM can be acquired by time-domain measurements (time-correlated single-photon counting) or frequency-domain measurements (with PMT modulation or digital frequency domain acquisition) in a confocal setup, or with wide-field systems (using time-gated cameras). In the best cases, the resulting data is analyzed in terms of multicomponent fluorescence lifetime decays with demanding requirements in terms of signal level (and therefore limited frame rate). Recently, the phasor approach has been proposed as a powerful alternative for fluorescence lifetime analysis of FLIM, ensemble, and single-molecule experiments. Here we discuss the advantages of combining phasor analysis with a new type of FLIM acquisition hardware presented previously, consisting of a high temporal and spatial resolution wide-field single-photon counting device (the H33D detector). Experimental data with live cells and quantum dots will be presented as an illustration of this new approach.